Analisis Self Efficacy Siswa dalam Menyelesaikan Masalah Matematika Berdasarkan Tingkat Kemampuan Siswa: Self Efficacy Siswa - Purnama Sari, Mega; Nur Azizah, Siti; M. Mahrus Asrori (Universitas KH. Mukhtar Syafaat Banyuwangi, 2023)
The background of this research is that there are students who do not like mathematics because students think mathematics is the most difficult subject in school. Many factors cause students to experience difficulties in learning mathematics so that they affect learning outcomes, both from within the student and from outside the student. This study aims to describe self-efficacy with high mathematical abilities, self-efficacy with moderate mathematical abilities, and self-efficacy with low mathematical abilities in solving mathematical problems. This research is a qualitative research. The subjects in this study were class VII students of SMP Nuris Jember, East Java. This study will analyze students' self-efficacy in solving social arithmetic math problems. Observations made are the results of student self-efficacy work and interviews with students. The collected settlement results will be analyzed using self-efficacy indicators. The results showed that the self-efficacy of students with high mathematical abilities could solve math problems well and meet all self-efficacy indicators. Students with moderate mathematical abilities can solve math problems well but only meet two indicators of self-efficacy, namely level and strength indicators. Students with low mathematical abilities have not been able to solve all the questions correctly and have not fulfilled all self-efficacy indicators.